Proceedings of the 1993 World Marketing Congress - Sirgy, M. Joseph (Springer, 2015)
This volume includes the full proceedings from the 1993 World Marketing Congress held in Istanbul, Turkey. The focus of the conference and the enclosed papers is on marketing thought and practices from a global perspective. This volume resents papers on various topics including marketing management, marketing strategy, and consumer behavior.